Incidents of the elimination of the royalty deduction, proposed in the 2022 Tax Reform project (2022)
The following essay aims to analyze the economic and social impacts that could be caused by the approval of the tax reform bill regarding the prohibition of the deduction of royalties in the income tax of companies in the mining and hydrocarbon sectors. At the initiative of the national government, Bill 118 of 2022 was filed before the Congress of the Republic, which contains within its tax reform proposals to eliminate the possibility of deducting the value paid for royalties from the taxable base of the income tax; These resources that are administered in the SGR, by constitutional mandate and regulated in Law 2056 of 2020, are distributed among the departments and municipalities in such a way that they can guarantee equity and regional development, based on the financing of investment projects aimed at satisfying the basic needs of the population. In this sense, it is necessary to analyze the impact of the elimination of the deduction of royalties proposed in the 2022 Tax Reform project for the mining and hydrocarbon sectors in Colombia, and also explain how this variation in the taxable base of the income tax could positively or negatively affect the economic and social stability of the country, since it is important to remember that the resources of the SGR come almost entirely from the extractive sectors, which are also sectors of the economy that generate income for the country, are sectors of the economy that voluntarily or contractually generate social investment works in the populations most influenced by their activity, thus contributing not only economically but also to the social development of populations that are generally isolated from large cities and that due to their demographic conditions find it difficult to generate resources from other economic activities.